Book review: What the ballot boxes (don’t) say: the political future of Latin America - Emma Turiño González (Revista CIDOB d'Afers Internacionals)
Review of the book: Alcántara Sáez, Manuel; García Montero, Mercedes y Bohigues, Asbel (coords.). Elecciones en América Latina: de pandemia y de derrotas (2020-2023) [Volumen 1]. Centro de Estudios Políticos y Constitucionales. Mº de la Presidencia, 2024, 406 págs.